Agri-horti-silvi system for production stability in arid zone - Yadava, N. D.; Soni, M. L.; Rathore, V. S.; Nathawat, N. S. (Indian Farming, 2018)
Indian arid zone agriculture showed fragile ecosystem with poor rainfall, frequent occurrence of drought, high temperature and poor soil resulting in failure of annual crops. The perennial fruit and silviculture trees provide an insurance against the complete crop failure having resistant to drought than crops. Agri-silvi-horti system provided more and multiple produce in one time from the same piece of land. The total system productivity is also higher than the sole cropping of crops or horticulture.